Is the first seizure epilepsy—and when?. (27th July 2015) - Lawn, Nicholas; Chan, Josephine; Lee, Judy; Dunne, John
Summary Objective Epilepsy has recently been redefined to include a single unprovoked seizure if the probability of recurrence is ≥60% over the following 10 years. This definition is based on the estimated risk of a third seizure after two unprovoked seizures, using the lower‐limit 95% confidence interval (CI) at 4 years, and does not account for the initially high recurrence rate after first‐ever seizure that rapidly falls with increasing duration of seizure freedom. We analyzed long‐term outcomes after the first‐ever seizure, and the influence of duration of seizure freedom on the likelihood of seizure recurrence, and their relevance to the new definition of epilepsy. Methods Prospective analysis of 798 adults with a first‐ever unprovoked seizure seen at a hospital‐based first seizure clinic between 2000 and 2011. The likelihood of seizure recurrence was analyzed according to the duration of seizure freedom, etiology, electroencephalography (EEG), and neuroimaging findings. Results The likelihood of seizure recurrence at 10 years was ≥60% in patients with epileptiform abnormalities on EEG or neuroimaging abnormalities, therefore, meeting the new definition of epilepsy. However, the risk of recurrence was highly time dependent; after a brief period (≤12 weeks) of seizure freedom, no patient group continued to fulfill the new definition of epilepsy. Of 407 patients who had a second seizure, the likelihood of a third seizure at 4 years was 68% (95% CI 63–73%) and at 10 years was 85% (95% CI 79–91%). Significance The duration of seizure freedom following first‐ever seizure substantially influences the risk of recurrence, with none of our patients fulfilling the new definition of epilepsy after a short period of seizure freedom. When a threshold was applied based on the 10‐year risk of a third seizure from our data, no first‐seizure patient group ever had epilepsy. These data may be utilized in a definition of epilepsy after a first‐ever seizure.